OPTIMALISASI PERAN DAN TANGGUNG JAWAB BALAI PEMASYARAKATAN (BAPAS) DALAM PELAKSANAAN SISTEM PERADILAN PIDANA ANAK DI SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 - Muhammad Rizal Muttaqien (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT Roles and Responsibilities Optimalisai Correctional Center (BAPAS) Children in the Criminal Justice System by Act No. 12 of 2012 of course we focused on remedies, for children in conflict with the law for law enforcement, including PK Correctional Center (BAPAS) where with all interested parties together to resolve the matter Children with Restorative Justice approach.The purpose in writing this law is to determine how the process of enforcement of children in conflict with the law or the perpetrator of the level of containment / investigation, prosecution and court decisions as well as mentoring and coaching community (PK) Correctional Center (BAPAS) in accordance with Law No. 11 In 2012 tentan Pperadilan child Criminal System which guarantees legal protection terhadapan children fiber isolates children from litigation and pemindanaan are not good for the soul, dignity and the future of the child.From the research found a variety of obstacles and barriers in the judicial process of the implementation of the Child which law enforcement is essential, both concerning quality and quality including Supervisor Performance Society (PK) Correctional Center (BAPAS) preformance implementation of Law No. 11 of 2012 on the Justice System criminal Children are not optimal given the vast area of performance Correctional Center (BAPAS) Class II Samarinda.                                                                                                              It is hoped that law enforcement officials must give priority to Restorative Justice in each case the Son as actors for the realization of justice according to conscience and justice memepertimbangakan on the terms of legislation so that the settlement is done Child Crime Pemindanaanya must be the last action.